KAITAN ASPEK STATUS SOSIAL PETANI SAYUR TERHADAP JENIS SUMBER INFORMASI YANG DIMANFAATKAN DI KELURAHAN LINGKAR SELATAN KECAMATAN JAMBI SELATAN KOTA JAMBI - Nida Kemala; Wiwin Alawiyah (Jurnal MeA (Media Agribisnis), 2016)
AbstractThis research had been held in Lingkar Selatan Village which focusing to learn the description of social status of farmer,  information source that used by them and the relationship between those variables.  Social status were indikated in three cases e.g.  education, land wide and the respodent  role in its siciety.  There were 41 samples that selected  by  simple  random  sampling method.  Description  method  was  used to  analyzed    those variables and Chi–Square 2x2 was applied to analyzed the relationship between them.The result of this research should be expected to be a foundation in deciding by the authority  in   selecting a   agricultural   information  transfer   system   which   considered the various information sources.   Instead  of  this consideration the information should be correctly  transferred.  The  result  of  this  research  showed   that   the   farmer number that has  low   education  category (63%)  was  higher  than  the  high  one (37%). The low  category of  land wide  was  dominant  (66%).  Only   three   farmers   that   had   authority   role   and all of them had showed hight category of information source useness. It showed 59% (24 farmers) have hight category of information source useness while 41% (17 farmers) showed low category of it useness and 16 farmers not used electronic information source yet. The farmer authority showed a significant relationship with information source useness, while education dan land wide had no relationship significantly with it. Keyword : Social Status, Extension, Information source, Farmer